Joint Trust Analysis and Artificial Gorilla Troops Optimization for Performance Improvement in UAVs-Assisted Vehicular Network - Adil Khan; Shabeer Ahmad; Sanam Shahla Rizvi; Ihsan Ali; Asad Ullah; Se Jin Kwon (IEEE Access, 2024)
The integration of unmanned aerial vehicles (UAVs) in the fifth-generation (5G) network has emerged as a promising solution to deliver seamless services and provide connectivity because of their mobile nature. In vehicular networks, connectivity between vehicles and the network can be affected by ground-level obstacles and false messages created by some deceitful vehicles. UAVs are integrated into vehicular networks to provide line-of-sight communication. This integration also poses specific challenges, such as maintaining reliable communication links and handling operational complexities related to coordination and routing, which minimizes the network throughput and packet delivery ratio (PDR) and increases energy consumption, routing overhead, and communication delay. This paper proposes improved trust analysis and artificial gorilla troops optimization (ITA-AGTO) to address the challenges associated with the security and deployment of UAVs in vehicular networks. ITA improves network security and reduces congestion by discarding incoming messages from a deceitful vehicle. It filters false messages by calculating the trust values corresponding to every message and determining whether to accept or discard the incoming message. The artificial gorilla troops optimization (AGTO) approach positions the UAVs and finds the optimal solution to transmit the data sent by the RSU or vehicle to a destination directly or through the ground base station. AGTO enhances communication intelligence and reduces the complexity of the network, thereby contributing to an overall performance improvement. The proposed approach is evaluated in terms of packet delivery ratio (PDR), communication delay, network throughput, energy efficiency, energy consumption, and routing overhead. Simulation results validate the effectiveness of the proposed approach over state-of-the-art approaches by achieving a maximum PDR (93.28%), throughput (658.17 Kbps), energy efficiency (88.19%), minimum routing overhead (865 packets), energy consumption (1.13 KJ) and communication delay (125.46 ms). The findings indicate the superior performance of the ITA-AGTO approach.